2019
DOI: 10.1063/1.5086953
|View full text |Cite
|
Sign up to set email alerts
|

Computationally efficient locally linearized constitutive model for magnetostrictive materials

Abstract: This paper presents a computationally efficient constitutive model for magnetostrictive materials. High computational efficiency is achieved through the use of local linearization (about easy axes) and discrete energy-averaging techniques. The model is applied to iron-gallium alloys (Galfenol) and tested for different magnetic field orientations relative to the easy axes. It is observed that the model accurately predicts both sensing and actuation characteristics while reducing the computation time by a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…James Prescott Joule performed the first measurements of magnetostriction by quantifying the change in length of magnetized iron samples. The Joule effect can be described by the following equation [42]:…”
Section: Magnetostrictive and Electrostrictive Materialsmentioning
confidence: 99%
“…James Prescott Joule performed the first measurements of magnetostriction by quantifying the change in length of magnetized iron samples. The Joule effect can be described by the following equation [42]:…”
Section: Magnetostrictive and Electrostrictive Materialsmentioning
confidence: 99%
“…This has resulted in common simplifying assumptions including zero exchange coupling (i.e., paramagnetic behavior) [41][42][43][44], potentially with simplified magnetocrystalline anisotropies that treat polycrystalline cubic materials as transversely isotropic [43][44][45][46]. Improving the computational efficiency of these models has been the focus of recent research that has shown an excellent ability to fit these models to experimental data [20,41,43,[45][46][47].…”
Section: Introductionmentioning
confidence: 99%